2023
DOI: 10.3390/ijms24021317
|View full text |Cite
|
Sign up to set email alerts
|

Domain Truncation in Hispidin Synthase Orthologs from Non-Bioluminescent Fungi Does Not Lead to Hispidin Biosynthesis

Abstract: Hispidin is a polyketide found in plants and fungi. In bioluminescent fungi, hispidin serves as a precursor of luciferin and is produced by hispidin synthases. Previous studies revealed that hispidin synthases differ in orthologous polyketide synthases from non-bioluminescent fungi by the absence of two domains with predicted ketoreductase and dehydratase activities. Here, we investigated the hypothesis that the loss of these domains in evolution led to the production of hispidin and the emergence of biolumine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…The domain architecture of ShPKS1 was AMP-ACP-KS-AT-DH-KR-ACP-ACP. It is similar to the hispidin synthase of H. sublateritium (AMP-ACP-KS-AT-DH-KR-ACP) [ 11 ]. Thus, ShPKS1 is a putative hispidin synthase in S. sanghuang .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The domain architecture of ShPKS1 was AMP-ACP-KS-AT-DH-KR-ACP-ACP. It is similar to the hispidin synthase of H. sublateritium (AMP-ACP-KS-AT-DH-KR-ACP) [ 11 ]. Thus, ShPKS1 is a putative hispidin synthase in S. sanghuang .…”
Section: Resultsmentioning
confidence: 99%
“…The hispidin synthase (HispS) of bioluminescent fungi has a AMP-ACP-KS-AT-ACP domain architecture. Moreover, the HispS in non-bioluminescent fungi has more DH and KR domains, and its domain architecture is AMP-ACP-KS-AT-DH-KR-ACP [ 11 ]. In the present study, we found that ShPKS1 (AMP-ACP-KS-AT-DH-KR-ACP-ACP) is a putative HispS.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations